Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran PAI Dengan Menggunakan Variasi Media Belajar - Mukhlis Mukhlis; Frenky Mubarok (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2021)
Islamic religious education is an effort to regulate students to know, understand, live, and believe in the teachings of the Islamic religion, coupled with religion to respect adherents of other religions in practice with inter-religious harmony, to realize national unity and unity. Learning using a variety of media in the subject of Islamic Religious Education (PAI) aims to eliminate boredom and revive in the teaching and learning process. The method used in this research is the quantitative approach, which is systematic, structured, and structured research from beginning to end, using data in the form of numbers as an analytical tool to conduct a study of what has been researched. Based on the results of the formative test in cycle I learning completeness reached 74% with an average value of 6.7, in cycle II student learning completeness rose to 85% with an average value of 8.0, and in submative student learning completeness was 79% with a value an average of 8.0. Keywords: Variation of Learning Media, Learning Interest, PAI Learning